2015
DOI: 10.1111/bjet.12273
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Learning design, teacher inquiry into student learning and learning analytics: A call for action

Abstract: This special issue deals with three areas. Learning design is the practice of devising effective learning experiences aimed at achieving defined educational objectives in a given context. Teacher inquiry is an approach to professional development and capacity building in education in which teachers study their own and their peers' practice. Learning analytics use data about learners and their contexts to understand and optimise learning and the environments in which it takes place. Typically, these three-desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
145
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 30 publications
1
145
1
6
Order By: Relevance
“…Persico, Pozzi [12] argued that the learning process should not only depend on experience, or best practices of colleagues but also pre-existing aggregated data on students' engagement, progression, and achievement. In a similar manner, Mor et al [13] suggested that LA could facilitate teacher inquiry by transforming knowledge from tacit to explicit, and perceive students and teachers as participants of a reflective practice. For instance, in a study of 148 learning designs by Toetenel, Rienties [28], the introduction of a systematic LD initiative consisting of visualization of initial LDs and workshops helped educators to focus on the development of a range of skills and more balanced LDs.…”
Section: Aligning Learning Analytics and Learning Designmentioning
confidence: 98%
See 1 more Smart Citation
“…Persico, Pozzi [12] argued that the learning process should not only depend on experience, or best practices of colleagues but also pre-existing aggregated data on students' engagement, progression, and achievement. In a similar manner, Mor et al [13] suggested that LA could facilitate teacher inquiry by transforming knowledge from tacit to explicit, and perceive students and teachers as participants of a reflective practice. For instance, in a study of 148 learning designs by Toetenel, Rienties [28], the introduction of a systematic LD initiative consisting of visualization of initial LDs and workshops helped educators to focus on the development of a range of skills and more balanced LDs.…”
Section: Aligning Learning Analytics and Learning Designmentioning
confidence: 98%
“…Nonetheless, in line with [7,9], findings from LA research in the past have been rather limited to delivering actionable feedback, while ignoring the context in which the learning data is situated. Thus, there is an increasing interest to align LA with LD, as the former facilitates the transfer of tacit educational practice to an explicit rendition, while the latter provides educators with pedagogical context for interpreting and translating LA findings to direct interventions [10][11][12][13][14]. While there are abundant discussions on the value and impact of integrating LD into LA to improve teacher inquiry [13,14], only a few studies have empirically examined how teachers actually design their courses [15,16] and whether LD influences satisfaction, VLE behavior, and retention [9,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed an increased interest to leverage Learning Analytics (LA) to inform and support Learning Design (LD) [22,25,30]. One of the main benefits of aligning LA with LD is that LA could act as a reflective resource on how students actually behave compared to instructors' assumptions embedded in their LD, which has been echoed by many scholars [10,25].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main benefits of aligning LA with LD is that LA could act as a reflective resource on how students actually behave compared to instructors' assumptions embedded in their LD, which has been echoed by many scholars [10,25]. Although substantial progress has been made within the LAK community to link how instructors' LD decisions with what students are doing [1,22,27,32,33], one major methodological challenge that is often ignored is the synchronization of the concept of time between LD and LA.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in line with [26,44] findings from LA research in the past have been rather limited to delivering actionable feedback, while ignoring the context of which the learning data is situated. Thus, within the LAK community there is an increasing interest to align LA with LD, as the former facilitates the transfer of tacit educational practice to an explicit rendition, while the latter provides educators with pedagogical context for interpreting and translating LA findings to direct interventions [3,33,34,37,40]. While there are abundant discussions on the value and impact of integrating LD into LA to improve teacher inquiry [3,37], only a few studies have empirically examined how teachers actually design their courses [4,20] and whether LD influences satisfaction, VLE behavior, and retention [42,44,45,48].…”
Section: Introductionmentioning
confidence: 99%